High-Technology Exports, Foreign Direct Investment, Renewable Energy Consumption and Economic Growth: Evidence from the United Arab Emirates - Shadab, Saima; Alam, Firoz (International Journal of Energy Economics and Policy, 2024)
Various attempts have been made to undercover the relationship between the UAE’s economic growth, FDI, and renewable energy, with inadequate focus on the role of high technology exports in the UAE. This paper, therefore, examines the short and long-term relationship between high-technology exports, foreign direct investment, renewable energy, and economic growth in the UAE for the period 1991-2020. For this purpose, the autoregressive distributed lag bounds testing approach to cointegration has been employed in this study. The short and long-run empirics reveal a positive and significant relationship between high technology exports and the UAE’s economic growth. Conversely, a significant negative relationship exists between renewable energy consumption and economic growth. Among various important findings, the long-run causality results show a unidirectional causality exists from high-tech exports to the UAE’s economic growth. Further, a bi-directional causality exists between FDI and high-tech exports, that in turn promotes economic growth of the UAE. Based on the overall results, the study provides important policy recommendations.